2023
DOI: 10.1200/go.22.00288
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Acute Lymphoblastic Leukemia: Clinical Characteristics, Treatment Outcomes, and Prognostic Factors: 10 Years' Experience From a Low- and Middle-Income Country

Abstract: PURPOSE Acute lymphoblastic leukemia (ALL) represents around 70% of pediatric leukemia. In high-income countries, the 5-year survival is above 90%, but survival in low- and middle-income countries is inferior. This study documents the treatment outcome and prognostic factors of pediatric ALL in Pakistan. MATERIALS AND METHODS In this prospective cohort study, all newly diagnosed patients with ALL/lymphoblastic lymphoma from age 1 to 16 years enrolled between January 1, 2012, and December 31, 2021, were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Also, patient dropout and treatment abandonment have been traditionally higher in Pakistan because of lack of finances, lost wages, and lack of social support. 27 Relapse rate in our study was 48.6%, which is higher than the documented relapse risk from Western data (30%-40%). 28,29 The possible reasons are lack of IHC on most samples resulting in missing out on high-grade B-cell lymphoma, nonavailability of rituximab in large number of patients, and use of CT scan for remission assessment after treatment.…”
Section: Discussioncontrasting
confidence: 68%
“…Also, patient dropout and treatment abandonment have been traditionally higher in Pakistan because of lack of finances, lost wages, and lack of social support. 27 Relapse rate in our study was 48.6%, which is higher than the documented relapse risk from Western data (30%-40%). 28,29 The possible reasons are lack of IHC on most samples resulting in missing out on high-grade B-cell lymphoma, nonavailability of rituximab in large number of patients, and use of CT scan for remission assessment after treatment.…”
Section: Discussioncontrasting
confidence: 68%
“…At the same time, other criteria, like time to relapse or location of relapse, are important factors for survival with B-ALL [13]. Similar studies in low-and middle-income countries found the age, gender, and initial WBC count to be prognostic markers for ALL in children [14]. In a separate study, children below 15 years had a very good prognosis with ALL (the survival rate exceeded 85%), which got worse with age.…”
Section: Initial Treatmentmentioning
confidence: 99%
“…Although 80% of newly diagnosed, pediatric cancer cases worldwide occur in LMICs, their outcomes are suboptimal for various reasons compared to those in high-income countries (HICs) [99]. Factors such as the inability to access cancer care facilities; delays in initiating treatment after symptom onset; discontinuation of treatment, such as maintenance therapy, especially in the outpatient setting; and inadequate supportive care have been identified as responsible for decreased overall survival in patients with pediatric ALL [100,101]. Many LMICs have limited resources for laboratory and radiological diagnostic equipment, which hinders or delays the accurate diagnosis of pediatric malignancies including ALL [102].…”
Section: Management Of All In Low-and Middle-income Countriesmentioning
confidence: 99%